Organization of banking activity in modern conditions - Yu Dian (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
Object of research is the operation system construction of China Construction Bank Jiangxi Branch, including organizational activities, risk management framework, technical implementation and compliance measures. Subject of research is the organization of banking activity in modern conditions how to deal with operational risks, implement financial technology, and adapt to the evolving economic and financial environment, in order to enhance the services to the real economy. Purpose of qualification master's work is Study the characteristics, challenges and development trends of banking activity organization under modern conditions, as well as the impact of financial technology on the traditional banking industry. According to results of the research, the importance of risk management is revealed, the role of fintech in risk prediction and mitigation is highlighted, the need for internal control and compliance is pointed out, as well as the importance of talent development and cross-departmental collaboration.
Організація банківської діяльності в сучасних умовах
Scientific advisor: Pohorelenko Nataliia, doctor of economics, professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; banking activity; commercial bank; banking; risk management; China construction bank